Accounting for Society: Examining the Interplay between Financial Reporting and Social Responsibility - Sutisman, Entar; Auliyah, Iriana; Noy, Ismail (Advances in Applied Accounting Research, 2024)
Purpose: This research explores the intersection of financial reporting and social responsibility by integrating Environmental, Social, and Governance (ESG) metrics into corporate financial reports. It aims to assess the impact of sustainability reporting frameworks on transparency and stakeholder engagement in the corporate sector. Research Design and Methodology: This study employs a systematic literature review and interpretive analysis to examine the existing theoretical and empirical literature on the evolution of financial reporting frameworks towards incorporating social responsibility. An interpretive approach through thematic analysis identifies key patterns and insights. Findings and Discussion: The results show a significant paradigm shift in financial reporting, with an increasing inclusion of ESG metrics alongside traditional financial information. This change is driven by regulatory requirements and stakeholder demand, with a focus on enhanced transparency and accountability. Challenges such as greenwashing and the authenticity of social responsibility claims persist, affecting standardization and data integrity. Implications: The findings underscore the need for more robust and standardized reporting frameworks to enhance the credibility and comparability of sustainability reports. Highlighting the importance of corporate accountability, the study suggests that integrating financial reporting with social responsibility is crucial for future research, particularly in terms of its impact on corporate reputation and stakeholder relations.